The differentiated school : making revolutionary changes in teaching and learning - Tomlinson, Carol A. (Gale virtual reference library., 2008)
Includes common misconceptions about differentiation; nonnegotiables that are essential to the implementation of differentiated instruction; factors that contribute to failure to change classroom practice; leadership lessons for accomplishing the change process; tools for monitoring and evaluating the change toward differentiation; and characteristics of staff development practices that support differentiated instruction.